The Effect of Cooperative Model-Integrated Huyula Local Wisdom Values on Mastery Concepts of Simple Machine Material - Primayanti, Tria; Odja, Abdul Haris; Yusuf, Muhammad; Abdjul, Tirtawaty; Ntobuo, Nova Elysia; Uloli, Ritin (Jurnal Pijar Mipa, 2025)
The learning model can be interpreted as a whole series of material presentations that include all aspects before, during and after learning. This study aims to examine the effect of applying a cooperative model integrated with local wisdom values on the mastery of the concept of simple aircraft research at SMP Negeri 1 Telaga Biru. The research design used a One-Shot Case Study by using one class as a sample. The results showed a significant increase in student learning outcomes after being treated using a cooperative model integrated with local wisdom values. The use of cooperative models integrated with local wisdom values increases the active involvement of students in discussions and cooperation, so as to improve understanding of concepts and the ability to carry out activities that are directly related to the concept of simple aircraft material. Data analysis shows that the average posttest score is higher than the learning objectives achievement criteria (KKTP). The results showed the criteria for testing the hypothesis of a one-sample t-test, tcount ≥ ttable, with α level = 0.05 for the experimental class, t table value (2.0096). This indicates that the cooperative model integrated with local wisdom values can improve students' learning outcomes in understanding the concept of simple aircraft material. This study concludes that the application of the cooperative model integrated with local wisdom values is effective because it involves students actively in the process of cooperation and discussion, thus strengthening their understanding of the material and achieving learning outcomes.